PENGETAHUAN IBU TENTANG PEMBERIAN MAKANAN PENDAMPING ASI PADA BAYI UMUR 6-12 BULAN DI DESA MANUNGGANG JAE KECAMATAN PADANGSIDIMPUAN TENGGARAPENGETAHUAN IBU TENTANG PEMBERIAN MAKANAN PENDAMPING ASI PADA BAYI UMUR 6-12 BULAN DI DESA MANUNGGANG JAE KECAMATAN PADANGSIDIMPUAN TENGGARA - EVA YUSNITA NASUTION (Jurnal Maternitas Kebidanan, 2020)
ABSTRACT Breast feeding food is the food given to babies after 6 months of age that can help meet the nutritional needs of infants, because the needs of the baby is no longer sufficient with breastfeeding alone (Riksani, 2012). This study aims to find out the description of mother's knowledge about feeding of breastfeeding supplement at 6-12 months old baby in Manunggang Jae Village, Padangsidimpuan Tenggara Sub-District, 2014. This research is descriptive, collecting data obtained through questionnaires, in which 40 respondents were studied by age , Education, employment, and information resources. Data processed by editing, coding and tabulating then analyzed and collected in the table followed by discussing the results of research with existing literature theory. The result of the research shows that majority of respondents are less knowledgeable, that is 22 respondents (55%), where the majority of respondents are 30-39 years old, 13 respondents (32.5%), majority with junior high school education level 17 respondents , 5%), the majority of farmers work as many as 12 respondents (30%), and the majority get source of information from friends and family as many as 14 respondents (35%). From the results of the research obtained respondents categorized less. To improve mother's knowledge about giving of breast milk to infants aged 6-12 months in need of cooperation between health worker with mother about giving of breast milk to baby age 6-12 month. Keywords : Knowledge, Mother, Babies 6-12 Months, MP-ASI.